Assessment of image quality using standard contrast injection and weight-based contrast injection protocols in Coronary CT Angiography - Noor Na’em, Noor Aina Dayana; Nor Azman, Nurul Dizyana; Mahmud, Mohd Hafizi (Faculty of Medicine, 2026)
Optimal contrast enhancement is crucial in Coronary Computed Tomography Angiography (CCTA) for accurate visualization of coronary arteries and cardiovascular disease diagnosis. The standard protocol employing a fixed contrast volume, may result in excessive contrast for smaller patients and insufficient enhancement for larger patients, thus leading to the risk of contrast-induced nephropathy and compromising diagnostic accuracy. This study assesses the image quality of CCTA images using a weight- based contrast injection protocol against a standard protocol.